Manufacturing method of stainless steel sintered mesh

The stainless steel sintered mesh manufacturing method addresses corrosion issues in hydrogen fuel cells by using an argon gas atmosphere during heat treatment, resulting in a durable and effective filter.

JP7661028B2Active Publication Date: 2025-04-14NIFCO INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020187946
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-11
Publication Date
2025-04-14
Estimated Expiration
2040-11-11

AI Technical Summary

Technical Problem

Stainless steel sintered meshes used as filters in hydrogen fuel cells can corrode in acidic environments, leading to inefficiencies and potential damage.

Method used

A manufacturing method for stainless steel sintered meshes involving a heat treatment process with controlled temperature and pressure conditions, specifically using an argon gas atmosphere to prevent chromium nitride formation and subsequent corrosion.

Benefits of technology

The method effectively prevents corrosion of the sintered mesh, ensuring its durability and effectiveness as a filter in hydrogen fuel cells, even in acidic environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661028000002
    Figure 0007661028000002
  • Figure 0007661028000003
    Figure 0007661028000003
  • Figure 0007661028000004
    Figure 0007661028000004
Patent Text Reader

Abstract

To provide a manufacturing method of a mesh which does not corrode even when the mesh composed of stainless steel is used as a filter for a hydrogen fuel cell under an acidic environment.SOLUTION: A manufacturing method of a sintered mesh includes a step of preparing a mesh 20 comprising austenitic stainless steel and including a plurality of wires 21, 22 extending in the mutually intersecting direction, and a heat treatment step of controlling the atmospheric temperature of the mesh. The heat treatment step includes a heating step for raising the ambient temperature to a treatment temperature, a holding step for holding the ambient temperature at the treatment temperature, and a temperature dropping step for lowering the ambient temperature. The processing temperature is equal to or higher than the austenitizing temperature. The temperature dropping step includes a quenching step of lowering the ambient temperature at a temperature dropping rate of 3°C / min or more under argon gas atmosphere.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a stainless steel sintered mesh. [Background technology]

[0002] Filters for removing foreign matter contained in hydrogen fuel are known. For example, Patent Document 1 discloses the use of a stainless steel mesh as a filter. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-64699 A Summary of the Invention [Problem to be solved by the invention]

[0004] If a stainless steel mesh is used as a filter in the acidic environment of a hydrogen fuel cell, the mesh may corrode.

[0005] An object of the present invention is to provide a method for producing a stainless steel sintered mesh that can effectively solve these problems. [Means for solving the problem]

[0006] The present invention relates to a method for producing a sintered mesh, comprising the steps of: Providing a mesh made of austenitic stainless steel, the mesh including a plurality of wires extending in cross directions; A heat treatment process for controlling the atmospheric temperature of the mesh, The heat treatment process includes a temperature increasing process of increasing the atmosphere temperature to a treatment temperature, a temperature maintaining process of maintaining the atmosphere temperature at the treatment temperature, and a temperature decreasing process of decreasing the atmosphere temperature, The treatment temperature is equal to or higher than the austenitizing temperature, The temperature lowering step is a method for producing a sintered mesh, which includes a quenching step of lowering the atmospheric temperature at a temperature lowering rate of 3° C. / min or more in an argon gas atmosphere.

[0007] In the holding step of the method for producing a sintered mesh according to the present invention, the pressure of the atmosphere may be lower than atmospheric pressure.

[0008] In the temperature lowering step of the method for producing a sintered mesh according to the present invention, the pressure of the argon gas may be higher than atmospheric pressure.

[0009] In the method for producing a sintered mesh according to the present invention, the treatment temperature may be 980°C or higher and 1100°C or lower.

[0010] In the method for producing a sintered mesh according to the present invention, the sintered mesh may be used as a filter for hydrogen fuel. Effect of the Invention

[0011] According to the present invention, corrosion of the sintered mesh can be suppressed. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a perspective view showing an example of a filter device. [Diagram 2] FIG. 2 is a perspective view showing an example of a mesh filter. [Diagram 3] FIG. 2 is a plan view showing an example of a sintered mesh 20. [Figure 4] 4 is a cross-sectional view showing the sintered mesh 20 of FIG. 3 as viewed from the AA direction. [Diagram 5] FIG. 2 is a diagram showing an example of a heat treatment process. [Figure 6] FIG. 11 is a diagram showing another example of a heat treatment process. [Figure 7] FIG. 1 shows a roll containing mesh. [Figure 8] FIG. 1 is a diagram illustrating an example of a heat treatment method. [Figure 9] FIG. 2 is a diagram showing an example of a roll arrangement in a heat treatment process. [Figure 10] FIG. 1 is a diagram for explaining an immersion test. [Figure 11] FIG. 1 is a diagram for explaining an etching test. [Figure 12] FIG. 2 is a diagram showing the observation results of the sample of Example 1. [Figure 13] FIG. 13 is a diagram showing the observation results of the sample of Example 2. [Figure 14] FIG. 13 is a diagram showing the observation results of the sample of Example 3. [Figure 15] FIG. 13 is a diagram showing the observation results of the sample of Example 4. [Figure 16] FIG. 13 is a diagram showing the observation results of the sample of Example 5. [Figure 17] FIG. 1 is a diagram showing the observation results of a sample of Comparative Example 1. [Figure 18] FIG. 13 is a diagram showing the observation results of a sample of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the drawings accompanying this specification, the scale and aspect ratios have been appropriately changed and exaggerated from those of the actual objects for the sake of ease of understanding.

[0014] (Filter device) 1 is a perspective view showing an example of a filter device 1. The filter device 1 is used, for example, as a filter for hydrogen fuel. The filter device 1 is used, for example, in an FC (Fuel Cell) stack of a hydrogen fuel cell vehicle.

[0015] The filter device 1 includes a mesh filter 10 and a case 2 that holds the mesh filter 10. The case 2 is made of, for example, resin.

[0016] 2 is a perspective view showing an example of the mesh filter 10. The mesh filter 10 may include a cylindrical side surface and a bottom surface. The side surface of the mesh filter 10 is formed of a sintered mesh 20.

[0017] The hydrogen fuel is, for example, compressed hydrogen gas. The hydrogen fuel flows into the inside of the mesh filter 10 through the sintered mesh 20. When the hydrogen fuel passes through the sintered mesh 20, foreign matter in the hydrogen fuel is captured. The hydrogen fuel flows out from the bottom surface of the mesh filter 10.

[0018] (sintered mesh) 3 is a plan view showing an example of the sintered mesh 20. The sintered mesh 20 includes a plurality of first wires 21 extending in a first direction D1 and a plurality of second wires 22 extending in a second direction D2 intersecting the first direction D1. The first direction D1 may be perpendicular to the second direction D2.

[0019] Fig. 4 is a cross-sectional view showing the sintered mesh 20 of Fig. 3 as viewed from the direction AA. As shown in Fig. 4, the first wire 21 and the second wire 22 may have a circular cross section.

[0020] The first wire 21 and the second wire 22 are bonded by sintering in the up-down direction shown in Fig. 4. Sintering occurs by subjecting a mesh including the first wire 21 and the second wire 22 to a heat treatment. The bond by sintering may occur in a state where the first wire 21 is positioned above the second wire 22, as indicated by reference numeral 23, or in a state where the second wire 22 is positioned above the first wire 21, as indicated by reference numeral 24.

[0021] 3, the first wire 21 and the second wire 22 may be coupled such that the first bonds 23 and the second bonds 24 are alternately arranged in the first direction D1 and the second direction D2. Note that the positional relationship between the first wire 21 and the second wire 22 is not limited to the examples shown in FIGS. 3 and 4.

[0022] The sintered mesh 20 includes gaps 25 surrounded by two first wires 21 and two second wires 22. When the sintered mesh 20 is used in a hydrogen fuel filter, foreign matter having a size larger than the gaps 25 is captured by the sintered mesh 20.

[0023] The symbols S1 and S2 respectively represent the width of the first wire 21 and the width of the second wire 22. The symbol S3 represents the interval between two adjacent first wires 21. The symbol S4 represents the interval between two adjacent second wires 22. The widths S1, S2 and the intervals S3, S4 are determined according to the size of the foreign matter to be captured. Preferably, the sintered mesh 20 can capture foreign matter having a size of 200 μm or more.

[0024] The widths S1 and S2 are, for example, 30 μm or more, may be 50 μm or more, or may be 100 μm or more. The widths S1 and S2 are, for example, 500 μm or less, may be 300 μm or less, or may be 200 μm or less.

[0025] The intervals S3 and S4 are, for example, 50 μm or more, and may be 100 μm or more, or may be 150 μm or more. The widths S1 and S2 are, for example, 500 μm or less, and may be 300 μm or less, or may be 200 μm or less.

[0026] The sintered mesh 20 is made of austenitic stainless steel. The austenitic stainless steel contains 0.08% by weight or less of carbon (C), 1.00% by weight or less of silicon (Si), 2.00% by weight or less of manganese (Mn), 0.045% by weight or less of phosphorus (P), 0.030% by weight or less of sulfur (S), 8.00% by weight or more and 15.00% by weight or less of nickel (Ni), 16.00% by weight or more and 20.00% by weight or less of chromium (Cr), 3.00% by weight or less of molybdenum (Mo), and the balance being iron (Fe) and unavoidable impurities. As the austenitic stainless steel, SUS304, SUS316, SUS316L, etc. can be used. Table 1 shows examples of the compositions of SUS304, SUS316, and SUS316L. The units of the values ​​in Table 1 are weight percent. [Table 1]

[0027] Stainless steel is known as a material that is resistant to corrosion. However, the inventors have found that the sintered mesh 20 used as a hydrogen fuel filter may corrode if the heat treatment conditions of the sintered mesh 20 are inappropriate. Specifically, the inventors have found that the sintered mesh 20 is susceptible to corrosion if the heat treatment of the sintered mesh 20 is performed in a nitrogen atmosphere.

[0028] One of the reasons why the sintered mesh 20 corrodes is thought to be as follows. In the heat treatment, the sintered mesh 20 is held at a treatment temperature equal to or higher than the austenitizing temperature for a certain period of time. When the ambient temperature is raised from room temperature to the treatment temperature, or when the ambient temperature is lowered from the treatment temperature to room temperature, the sintered mesh 20 is exposed to an atmosphere at a temperature at which nitrides or carbides are likely to precipitate. For this reason, when the atmosphere contains nitrogen gas, nitrogen atoms may penetrate into the interior of the sintered mesh 20, resulting in the formation of chromium nitrides at grain boundaries and the like. When chromium nitrides are formed, the chromium concentration in the surrounding austenitic structure decreases. When the chromium concentration decreases, the resistance to corrosion decreases. As a result, corrosion may occur in the sintered mesh 20 used as a filter in the acidic environment of a hydrogen fuel cell. In the following description, the austenitic structure having a reduced chromium concentration is also referred to as a chromium-depleted layer. The above-mentioned reasons are merely examples, and even if the sintered mesh 20 corrodes for other reasons, the significance of the present invention is not lost.

[0029] When the sintered mesh 20 is used as a filter for hydrogen fuel, the sintered mesh 20 is required to capture fine foreign matter. For this reason, the widths S1, S2 of the first wire 21 and the second wire 22 constituting the sintered mesh 20 are made smaller. The smaller the widths S1, S2, the higher the ratio of the surface area of ​​the wires 21, 22 to the volume of the wires 21, 22. For this reason, a chromium-depleted layer is more likely to occur during heat treatment.

[0030] In order to solve this problem, the present invention proposes to carry out the heat treatment in an argon gas atmosphere. A method for producing the sintered mesh 20 will now be described.

[0031] (Method of manufacturing sintered mesh) First, a mesh is prepared that includes the first wire 21 and the second wire 22. The first wire 21 and the second wire 22 may or may not be bonded to each other by sintering or the like.

[0032] Next, a heat treatment step is performed to control the temperature of the atmosphere around the mesh. For example, the mesh is placed in a furnace and the temperature of the atmosphere in the furnace is controlled. The shape of the mesh during the heat treatment step is arbitrary. For example, a sheet of the mesh may be wound into a roll, and the roll may be subjected to the heat treatment.

[0033] Fig. 5 is a diagram showing an example of a heat treatment process. The horizontal axis of Fig. 5 represents time, the vertical axis on the left represents the temperature of the atmosphere, and the vertical axis on the right represents the pressure of the atmosphere. When the atmosphere is replaced with argon gas, the pressure of the atmosphere is the pressure of the argon gas. The heat treatment process includes a temperature increase step S10, a holding step S20, and a temperature decrease step S30. Each step will be described below.

[0034] In the temperature increasing step S10, the ambient temperature is increased from room temperature to a treatment temperature T2. The treatment temperature T2 is equal to or higher than the austenitizing temperature. At the treatment temperature T2, the austenitic structure of the austenitic stainless steel can exist stably. The treatment temperature T2 is, for example, 980°C or higher, and may be 1020°C or higher. The treatment temperature T2 is, for example, 1100°C or lower, and may be 1060°C or lower.

[0035] In a certain temperature range, for example, in the range of 500°C to 800°C, chromium nitrides or carbides are likely to precipitate in austenitic stainless steel. The temperature range in which nitrides or carbides are likely to precipitate is also called the precipitation temperature range. The lower limit of the precipitation temperature range is also called the precipitation temperature T1. The precipitation temperature T1 is, for example, 500°C.

[0036] The temperature increasing step S10 may include a rapid heating step S15 in which the ambient temperature is increased at a heating rate H1 of 5° C. / min or more. This allows the precipitation temperature range to be passed quickly. This makes it possible to suppress the generation of chromium nitrides or carbides on the mesh during the temperature increasing step S10. The heating rate H1 is calculated by dividing the difference between the treatment temperature T2 and the precipitation temperature T1 by the time required for the ambient temperature to increase from the precipitation temperature T1 to the treatment temperature T2. The heating rate H1 may be 10° C. / min or more, or may be 20° C. / min or more.

[0037] The temperature increasing step S10 is performed in an argon gas atmosphere having a first pressure P1. The first pressure P1 may be, for example, 10 Pa or more, or 50 Pa or more. The first pressure P1 may be, for example, 1 kPa or less, or 300 Pa or less.

[0038] In the holding step S20, the ambient temperature is held at the treatment temperature T2 for a certain period of time. At the treatment temperature T2, elements such as chromium, nickel, carbon, and nitrogen are dissolved in the austenite structure. Therefore, even if chromium nitrides or carbides are generated in the mesh, the constituent elements of the nitrides or carbides can be dissolved in the austenite structure by the holding step S20. This makes it possible to suppress the presence of a chromium-depleted layer in the mesh.

[0039] The time for which the atmospheric temperature is held at the treatment temperature T2 is, for example, 30 minutes or more, and may be 45 minutes or more. By holding the time for 30 minutes or more, elements such as chromium, nickel, carbon, and nitrogen can be dissolved in the austenite structure. The holding time is, for example, 90 minutes or less, and may be 60 minutes or less. By holding the time for 90 minutes or less, sintering of the mesh sheets wound into a roll can be suppressed.

[0040] The holding step S20 is performed under an argon gas atmosphere having a second pressure P2. The second pressure P2 may be, for example, 10 Pa or more, or 50 Pa or more. The second pressure P2 may be lower than atmospheric pressure. The second pressure P2 may be, for example, 1 kPa or less, or 300 Pa or less.

[0041] The temperature lowering step S30 lowers the ambient temperature from the treatment temperature T2 to room temperature. The temperature lowering step S30 may include a quenching step S35 in which the ambient temperature is lowered at a temperature lowering rate C1 of 3° C. / min or more. This allows the precipitation temperature range to be passed quickly. This makes it possible to suppress the generation of chromium nitrides or carbides on the mesh during the temperature lowering step S30. The temperature lowering rate C1 is calculated by dividing the difference between the treatment temperature T2 and the precipitation temperature T1 by the time required for the ambient temperature to drop from the treatment temperature T2 to the precipitation temperature T1. The temperature lowering rate C1 may be 5° C. / min or more, 10° C. / min or more, 20° C. / min or more, 50° C. / min or more, or 100° C. / min or more.

[0042] The holding step S20 may be performed under an argon gas atmosphere having a third pressure P3. The third pressure P3 may be higher than atmospheric pressure. The third pressure P3 may be, for example, 110 kPa or more, or 150 kPa or more. The second pressure P2 may be, for example, 600 kPa or less, or 200 kPa or less.

[0043] Fig. 6 is a diagram showing another example of the heat treatment process. As shown in Fig. 6, the temperature increasing process S10 may include a first temperature increasing process S11, a waiting process S12, and a second temperature increasing process S13. The first temperature increasing process S11 increases the ambient temperature from room temperature to a waiting temperature T4. The waiting process S12 holds the ambient temperature at the waiting temperature T4 for a certain period of time. The second temperature increasing process S13 increases the ambient temperature from the waiting temperature T4 to a treatment temperature T2.

[0044] When multiple rolls are simultaneously subjected to heat treatment, the temperature of the rolls may vary depending on the position of the rolls. In this case, the timing at which the temperature reaches the treatment temperature T2 may differ depending on the position of the roll. By including the waiting step S12 in the temperature increase step S10, it is possible to prevent the timing at which the temperature reaches the treatment temperature T2 from differing depending on the position of the roll. The waiting temperature T4 is, for example, 500°C or higher and 900°C or lower.

[0045] According to this embodiment, the temperature lowering step is performed in an argon gas atmosphere, thereby making it possible to suppress the generation of chromium nitrides or carbides in the sintered mesh 20. This makes it possible to suppress the generation of a chromium-deficient layer in the sintered mesh 20. This makes it possible to suppress the occurrence of corrosion in the sintered mesh 20 used as a filter in the acidic environment of a hydrogen fuel cell.

[0046] The use of the sintered mesh 20 is not limited to the filter of the hydrogen fuel cell, and the sintered mesh 20 of the present embodiment may be used in other environments where corrosion is likely to occur. EXAMPLES

[0047] Next, the present invention will be described more specifically with reference to examples. However, the present invention is not limited to the description of the following examples as long as it does not depart from the gist of the present invention.

[0048] Example 1 First, a mesh sheet including the first wire 21 and the second wire 22 was prepared. The mesh sheet had a width of 50 mm and a length of 10 m. The widths S1 and S2 of the first wire 21 and the second wire 22 were 50 μm. When the cross section of the first wire 21 and the second wire 22 is circular, the widths S1 and S2 are the so-called wire diameters. Next, as shown in FIG. 7, the mesh sheet 26 was wound into a roll. SUS316L containing 0.01% by weight of carbon was used as the material of the mesh sheet 26.

[0049] 8, the roll 30 of the mesh sheet 26 was placed in the holder 40. The holder 40 includes a first holder 41, a second holder 42, a third holder 43, and a fourth holder 44, which are stacked in this order from the bottom up. Twenty-five rolls 30 were placed in each of the holders 41 to 44.

[0050] FIG. 9 is a diagram showing the arrangement of the rolls 30 in each of the holders 41 to 44. As shown in FIG. 9, 5 columns and 5 rows of rolls 30 were arranged in each of the holders 41 to 44. In the subsequent evaluation, the roll marked with reference numeral 31 in FIG. 9 was used as an evaluation roll. Also, the roll marked with reference numeral 32 was used as a monitor roll for measuring the atmospheric temperature of the furnace. The evaluation roll 31 and the monitor roll 32 were arranged in the center of the second holder 42 and the third holder 43.

[0051] Next, the temperature of the furnace atmosphere was controlled while the holder 40 was placed in the furnace, the atmosphere of which was replaced with argon gas. In this way, the roll 30 was subjected to a heat treatment. The temperature profile of Fig. 6 was used as the temperature profile for the heat treatment. The conditions for the heat treatment were as follows. Heating rate H1 in the heating step S10: 20°C / min Standby temperature T4 of standby process S12: 860℃ (held for 30 minutes) Holding step S20 treatment temperature T2: 1100℃ (held for 60 minutes) Argon gas pressure during holding step S20: 100 Pa ·Cooling rate C1 of temperature dropping process S30: 100℃ / min Argon gas pressure during cooling process S30: 200kPa

[0052] The sintered mesh 20 obtained by the heat treatment was subjected to an immersion evaluation and an etching evaluation.

[0053] In the immersion evaluation, a solution 51 contained in a container 50 was prepared as shown in FIG. 10. The solution 51 was an acidic solution containing sulfuric acid. The pH of the solution 51 was 4.1. Next, the sample 35 cut out from the sintered mesh 20 was immersed in the solution 51 for 16 hours while the temperature of the solution 51 was controlled at 80° C. Thereafter, it was visually confirmed whether or not the sample 35 had discolored. No discoloration was observed.

[0054] In the etching evaluation, sample 35 was evaluated in accordance with JIS G0571:2003 "Oxalic Acid Etching Test Method for Stainless Steel." First, as shown in FIG. 11, the surface of sample 35 was polished to form test surfaces 36 on the surface of first wire 21 and the surface of second wire 22. Next, sample 35 was immersed in a 10% oxalic acid solution. Next, sample 35 was electrolytically etched using test surface 36 as an anode. Next, the surface of sample 35 was observed using a scanning electron microscope.

[0055] The results of the observation are shown in Figure 12. The first image, labeled 61, corresponds to the state shown in Figure 11. The second image, labeled 62, is an enlarged portion of the first image 61. As shown in the second image 62, no sensitization occurred.

[0056] Example 2 As in Example 1, a roll 30 of mesh sheet 26 was produced using SUS316L containing 0.01% by weight of carbon. Widths S1, S2 of the first wire 21 and the second wire 22 were 50 μm. Then, as in Example 1, the roll 30 was subjected to heat treatment using the holder 40. The temperature profile of FIG. 6 was used as the temperature profile for the heat treatment. The conditions for the heat treatment were as follows: Heating rate H1 in the heating step S10: 20°C / min Standby temperature T4 of standby process S12: 860℃ (held for 30 minutes) Holding step S20 treatment temperature T2: 1100℃ (held for 60 minutes) Argon gas pressure during holding step S20: 100 Pa ·Cooling rate C1 of temperature cooling process S30: 65℃ / min Argon gas pressure during cooling process S30: 110kPa

[0057] As in Example 1, the sintered mesh 20 obtained by the heat treatment was subjected to an immersion evaluation and an etching evaluation. No discoloration was observed in the immersion evaluation. The images obtained in the etching evaluation are shown in FIG. 13. As shown in the second image 62, no sensitization occurred.

[0058] Example 3 As in Example 1, a roll 30 of mesh sheet 26 was produced using SUS316L containing 0.01% by weight of carbon. Widths S1, S2 of the first wire 21 and the second wire 22 were 50 μm. Then, as in Example 1, the roll 30 was subjected to heat treatment using the holder 40. The temperature profile of FIG. 6 was used as the temperature profile for the heat treatment. The conditions for the heat treatment were as follows: Heating rate H1 in the heating step S10: 20°C / min Standby temperature T4 of standby process S12: 860℃ (held for 30 minutes) Holding step S20 treatment temperature T2: 1100℃ (held for 60 minutes) Argon gas pressure during holding step S20: 100 Pa ·Cooling rate C1 of temperature dropping process S30: 3.3℃ / min Argon gas pressure during cooling process S30: 110kPa

[0059] As in Example 1, the sintered mesh 20 obtained by the heat treatment was subjected to an immersion evaluation and an etching evaluation. No discoloration was observed in the immersion evaluation. The images obtained in the etching evaluation are shown in FIG. 14. As shown in the second image 62, no sensitization occurred.

[0060] Example 4 As in Example 1, a roll 30 of mesh sheet 26 was produced using SUS316L containing 0.01% by weight of carbon. Widths S1, S2 of the first wire 21 and the second wire 22 were 50 μm. Then, as in Example 1, the roll 30 was subjected to heat treatment using the holder 40. The temperature profile of FIG. 6 was used as the temperature profile for the heat treatment. The conditions for the heat treatment were as follows: Heating rate H1 in the heating step S10: 10°C / min Standby temperature T4 of standby process S12: 600℃ (held for 30 minutes) Holding step S20 treatment temperature T2: 1020℃ (held for 30 minutes) Argon gas pressure during holding step S20: 100 Pa ·Cooling rate C1 of temperature dropping process S30: 100℃ / min Argon gas pressure during cooling process S30: 200kPa

[0061] As in Example 1, the sintered mesh 20 obtained by the heat treatment was subjected to an immersion evaluation and an etching evaluation. No discoloration was observed in the immersion evaluation. The images obtained in the etching evaluation are shown in FIG. 15. As shown in the second image 62, no sensitization occurred.

[0062] Example 5 A roll 30 of mesh sheet 26 was produced in the same manner as in Example 1, except that SUS316 containing 0.04% by weight of carbon was used. Widths S1, S2 of the first wire 21 and the second wire 22 were 50 μm. Next, similarly to Example 1, the roll 30 was subjected to heat treatment using the holder 40. The temperature profile of FIG. 6 was used as the temperature profile for the heat treatment. The heat treatment conditions were as follows: Heating rate H1 in the heating step S10: 20°C / min Standby temperature T4 of standby process S12: 860℃ (held for 30 minutes) Holding step S20 treatment temperature T2: 1100℃ (held for 60 minutes) Argon gas pressure during holding step S20: 100 Pa ·Cooling rate C1 of temperature dropping process S30: 100℃ / min Argon gas pressure during cooling process S30: 200kPa

[0063] As in Example 1, the sintered mesh 20 obtained by the heat treatment was subjected to an immersion evaluation and an etching evaluation. No discoloration was observed in the immersion evaluation. The images obtained in the etching evaluation are shown in FIG. 16. As shown in the second image 62, no sensitization occurred.

[0064] Comparative Example 1 As in Example 1, a roll 30 of mesh sheet 26 was produced using SUS316L containing 0.01% by weight of carbon. The widths S1, S2 of the first wire 21 and the second wire 22 were 50 μm. Next, the roll 30 was subjected to a heat treatment using a holder 40. The temperature profile of FIG. 6 was used as the temperature profile for the heat treatment. The temperature lowering step S30 was carried out in an atmosphere replaced with nitrogen gas. The heat treatment conditions were as follows. Heating rate H1 in the heating step S10: 20°C / min Standby temperature T4 of standby process S12: 860℃ (held for 30 minutes) Holding step S20 treatment temperature T2: 1100℃ (held for 60 minutes) ·Cooling rate C1 of temperature dropping process S30: 100℃ / min Nitrogen gas pressure during cooling process S30: 200kPa

[0065] As in Example 1, the sintered mesh 20 obtained by the heat treatment was subjected to an immersion evaluation and an etching evaluation. No discoloration was observed in the immersion evaluation. The images obtained in the etching evaluation are shown in FIG. 17. As shown in the second image 62, sensitization occurred.

[0066] Comparative Example 2 As in Example 5, a roll 30 of mesh sheet 26 was produced using SUS316 containing 0.04% by weight of carbon. The widths S1 and S2 of the first wire 21 and the second wire 22 were 50 μm. Next, the roll 30 was subjected to a heat treatment using a holder 40. The temperature profile of FIG. 5 was used as the temperature profile for the heat treatment. The temperature lowering step S30 was carried out in an atmosphere replaced with nitrogen gas. The heat treatment conditions were as follows. Heating rate H1 in the heating step S10: 20°C / min Holding step S20 treatment temperature T2: 1100℃ (held for 60 minutes) ·Cooling rate C1 of temperature cooling process S30: 200℃ / min Nitrogen gas pressure during cooling process S30: 200kPa

[0067] As in Example 1, the sintered mesh 20 obtained by the heat treatment was subjected to an immersion evaluation and an etching evaluation. No discoloration was observed in the immersion evaluation. The images obtained in the etching evaluation are shown in FIG. 18. As shown in the second image 62, sensitization occurred. [Explanation of symbols]

[0068] 1 Filter device 2 Cases 10 mesh filter 20 Sintered Mesh 21 First Wire 22 Second Wire 30 rolls 31 Evaluation roll 32 Monitor roll 35 Samples 36 Test Surface

Claims

1. A method for producing a sintered mesh, comprising the steps of: Providing a mesh made of austenitic stainless steel, the mesh including a plurality of wires extending in cross directions; A heat treatment step of controlling the atmospheric temperature of the mesh, The heat treatment process includes a temperature increasing process of increasing the atmosphere temperature to a treatment temperature, a temperature maintaining process of maintaining the atmosphere temperature at the treatment temperature, and a temperature decreasing process of decreasing the atmosphere temperature, The treatment temperature is equal to or higher than the austenitizing temperature, The temperature decreasing step includes a rapid cooling step of decreasing the atmospheric temperature at a temperature decreasing rate of 3° C. / min or more under an argon gas atmosphere, A method for producing a sintered mesh, wherein in the temperature decreasing step, the pressure of the argon gas is higher than atmospheric pressure.

2. The method for producing a sintered mesh according to claim 1 , wherein the treatment temperature is 980° C. or higher and 1100° C. or lower.

3. The method for producing a sintered mesh according to claim 1 or 2, wherein the sintered mesh is for use as a filter for hydrogen fuel.

Citation Information

Patent Citations

  • Isolation material and preparation method thereof

    CN108579209A

  • Production of wire gauze

    JP1989034537A

  • Method and device for joining material

    JP1995080662A

  • Dry corrosion resistance heat treatment of stainless steel and stainless steel

    JP1997071812A

  • Production of stainless steel strip small in unevenness of gloss

    JP2000328142A